PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PENGOLAHAN HASIL TERNAK BERUPA SUSU PASTEURISASI DI PONDOK PESANTREN DARUSSALAM PURWOKERTO - Zulaikhah, Siti Rahmawati; Mustikasari, Dian; Karseno, Karseno (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Darussalam Islamic Boarding School Purwokerto is a partner in this community empowerment activity.  Boarding School students consist of various statuses, some are still studying in Junior High School, Senior High School and students of University.  Based on the results of the situation analysis, there is a problem being faced, namely that there are still many students whose personal skills in knowledge and skills regarding the processing of livestock products in the form of milk are still low.  In fact, the city of Purwokerto has regional potential as a source of dairy milk production because it has highland geography, for example Baturraden. Apart from that, Darussalam Boarding School has a shop that sells various kinds of student needs, so it can be used to improve the cottage economy, especially by empowering students to produce their own products by exploiting the region's potential, for example processing dairy cow's milk into pasteurized milk of various flavors.  The solution offered to overcome this problem is to provide technology transfer in the form of making various flavors of pasteurized milk.  This solution was chosen because making pasteurized milk uses simple technology, but can produce a product that has a longer shelf life because pathogenic bacteria have been killed.  The method used is: 1) Surveys and interviews to determine problems, 2) Socialization regarding the processing of livestock products in the form of milk, 3) Training, demonstrations and assistance in making various flavors of pasteurized milk, 4) Evaluation of the implementation of service.  The result of this service is that a formula for pasteurized milk with various flavors is obtained with the formula for one liter of milk adding ± 100 grams of granulated sugar, and ± 5 ml of various flavors.  The evaluation results from the pre test and post test showed an increase of 20.62%.  The conclusion obtained is that this service in the context of community empowerment with Darussalam Islamic Boarding School Purwokerto partners has succeeded in increasing the level of knowledge, understanding and skills of students in adopting the science and technology of processing livestock products in the form of milk into pasteurized milk of various flavors.